Role and Status of Antecedent Characteristics of Dairy Farmers in Quality Milk Production - Singh, Vikram; Gupta, Jancy; Nain, M S (Indian Journal of Extension Education, 2016)
Raw milk quality is important in dairy value chain, where dairy farmer is the key client, who decides the shelf life of milk  and milk products. To know about the impact of milk quality improvement programmes like Clean Milk Production,  policy makers should know about the antecedent characteristiced dairy farmers. This study was conducted with this  objective in Rajasthan state, where 120 dairy farmers from four district milk unions were selected by using multistage  proportionate random sampling method. The results of the study revealed that, a large majority of dairy farmers were  belonging to middle age group (34 to 51 years), 26.70 per cent dairy farmers were illiterate, followed by 19.20 per cent  belonging to metric level education. Half of the respondents were found belonging to the medium category regarding their  family education status. A large number of dairy farmers (80%) were found belonging in medium category for their  experience in dairying i.e. 13 to 30 years. Majority of dairy farmers (70.84%) were having medium family size i.e. 6 to 9  members and social participation (68.34%). The 40.84 per cent dairy farmers were possessing medium land holding (2 to  4 ha.) 3 - 9 animals, Whereas 34.20 per cent dairy farmers were having their annual income between `1, 00,001 to ` 1, 50,000 per annum.
Keywords: CMP; DCS; dock; milk quality; socio-economic; socio-personal